Niemieckie wizje kształtu Unii Europejskiej w okresie rządów Gerharda Schrödera - KŁYS, JUSTYNA (Rocznik Integracji Europejskiej, 2012)
The unusual activity of the Federal Republic of Germany during all integration processes in Europe was questioned after Gerhard Schröder’s victory in the 1998 election. The Social Democratic Party of Germany (SPD – Sozialdemokratische Partei Deutschlands), which for many years had been pushed into opposition, did not have a clear vision of its European policy, which gave rise to concerns from European partners. In addition, the coalition government of the SPD-Union 90/The Greens emphasized German interests in European politics more strongly than Christian Democratic governments.With a persistence that had never been seen before, they demanded that the financial burdens of the Federal Republic of Germany towards the EU budget be reduced and the Common Agricultural Policy be reformed, thereby giving up the „checkbook policy”. One of the focal points became the reform of the European Union’s institutional system and decision-making process. Joschka Fischer’s „From a union of states to a federation” speech, related to the reform of the EU, delivered in May 2000, marked a breakthrough and started an international debate on the political form of the Union. The author of this paper presents German ideas on European integration and visions of the form of the European Union from 1998–2005.